CHANGES IN MITOCHONDRIAL FUNCTION AND STRUCTURE WITHIN PANCREATIC BETA CELLS OF INDIVIDUALS WITH TYPE 2 DIABETES (International journal of medical sciences, 2026)
Aims: There is limited knowledge regarding the insulin secretion characteristics of pancreatic islets derived from individuals with type 2 diabetes. Given that mitochondria play a central role in generating key metabolites that regulate insulin release, we investigated both insulin secretion and mitochondrial function and morphology in islets isolated from type 2 diabetic patients.Methods: Pancreatic islets were isolated using collagenase digestion followed by density gradient purification. Insulin secretion in response to glucose and arginine was measured using the batch incubation method. Additionally, adenine nucleotide levels, mitochondrial membrane potential, expression of UCP-2, respiratory chain complexes I and V, and nitrotyrosine content were assessed and analyzed in relation to insulin secretion.Results: Compared with control islets, islets from diabetic patients exhibited diminished insulin secretion in response to glucose. This defect was accompanied by reduced ATP content, a decreased ATP/ADP ratio, and impaired mitochondrial membrane hyperpolarization. Type 2 diabetic islets also showed increased protein expression of UCP-2, complexes I and V, and elevated nitrotyrosine levels. Morphological analysis revealed that while the number of mitochondria in beta cells was similar between diabetic and control groups, mitochondrial volume density was significantly greater in diabetic beta cells.Conclusions: In pancreatic beta cells from type 2 diabetic subjects, impaired glucose-stimulated insulin secretion is closely associated with substantial alterations in mitochondrial function and structure. Notably, upregulation of UCP-2—likely reflecting a state of nutrient excess—results in decreased ATP production and a reduced ATP/ADP ratio, ultimately contributing to diminished insulin release.